2020
DOI: 10.1097/bot.0000000000001903
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of PCR Screening in the Initial Triage of Trauma Patients During COVID-19 Pandemic

Abstract: Background: Hospitals worldwide have postponed all nonessential surgery during the COVID-19 pandemic, but non-COVID-19 patients are still in urgent need of care. Uncertainty about a patient's COVID-19 status risks infecting health care workers and non-COVID-19 inpatients. We evaluated the use of quantitative reverse transcription polymerase chain reaction (RT-qPCR) screening for COVID-19 on admission for all patients with fractures. Methods: We conducted a retrospective coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Knowing that 56% of COVID-19 patient present with no or only mild symptoms [23], this strategy may need to be re-evaluated. A retrospective study showed increased detection rates of COVID-19 for admitted orthopedic patients when testing all admitted patients compared with testing based on clinical suspicion (7.14% vs 33.3% after surgery) [24]. Our study could not establish whether limiting testing was due to significant variation in infection rates across provinces during the study period or due to potentially limited laboratory capacity.…”
Section: Discussionmentioning
confidence: 63%
“…Knowing that 56% of COVID-19 patient present with no or only mild symptoms [23], this strategy may need to be re-evaluated. A retrospective study showed increased detection rates of COVID-19 for admitted orthopedic patients when testing all admitted patients compared with testing based on clinical suspicion (7.14% vs 33.3% after surgery) [24]. Our study could not establish whether limiting testing was due to significant variation in infection rates across provinces during the study period or due to potentially limited laboratory capacity.…”
Section: Discussionmentioning
confidence: 63%
“…Porcel et al recommended evaluating all patients with the RT-PCR test to find asymptomatic, positive cases in trauma patients with low-energy fractures. 20 As mentioned above, we (and other low- and middle-income countries) cannot run this system due to our limitations.…”
Section: Discussionmentioning
confidence: 99%
“…One cohort study found that patients even if not having any symptoms still may be the carrier for viruses thus RT-PCR can detect those at genetic level. Thus, it helps in prevention of nosocomial infection and further spread unknowingly [10].…”
Section: Introductionmentioning
confidence: 99%
“…Self-collected saliva specimens was tested with 6 different molecular diagnostic tests like RTqPCR LDT, SARS-CoV-2 RAT, 3 direct RT-qPCR kits, and RT-LAMP and all tests showed a excellent results. Thus, based on these results, molecular diagnostic method has a great scope ahead [30]. Dr. Aneesh Mehta said that saliva test for coronavirus by PCR is the new type of diagnosis, as it is not invasive method but just spit is required as a sample [31].…”
Section: Introductionmentioning
confidence: 99%